Perluasan Makna Partisipasi Masyarakat dalam Pembentukan Undang-Undang Pasca Putusan Mahkamah Konstitusi - Dian Ayu Widya Ningrum; Al Khanif Al Khanif; Antikowati Antikowati (Jurnal Konstitusi, 2022)
Public participation is intended the idea of forming laws and regulations does not always have to come from the power holders only, but can emerge from the society. This paper aims to determine the impact of the Constitutional Court’s decision Number 91/PUU-XVIII/2020 on the formation of laws in Indonesia, especially in accommodating public participation which is limited to two main issues. First, how is the form of expanding the meaning of public participation in the Constitutional Court’s decision Number 91/PUU-XVIII/2020. Second, what is the impact of expanding the meaning of public participation in the formation of laws. This doctrinal legal research uses secondary data. The results of the study show that the form of expanding the meaning of public participation in the Constitutional Court’s decision Number 91/PUU-XVIII/2020 is carried out in a meaningful way, by providing guarantees of participation for affected communities and the impact of expanding the meaning of public participation in the formation of laws, namely changing the paradigm of law formation, improvement of regulations and strengthening of public participation as a basis for formal testing.